Connectionism : a hands-on approach - Dawson, Michael Robert William, 1959-; Wiley InterScience (Online service) (Oxford, UK ; Malden, MA : Blackwell Pub., 2005)
CONNNECTIONISM is a'hands on' introduction to connectionist modeling. Three different types of connectionist architectures - distributed associative memory, perceptron, and multilayer perceptron - are explored. In an accessible style, Dawson provides a brief overview of each architecture, a detailed introduction on how to use a program to explore this network, and a series of practical exercises that are designed to highlight the advantages, and disadvantages, of each and to provide a'road map' to the field of cognitive modeling. This book is designed to be used as a stand-alone volume, or a.
Ch. 25. Interpreting networks of value units -- Ch. 26. Interpreting distributed representations -- Ch. 27. Creating your own training sets.
Includes bibliographical references (pages 188-194) and indexes.
Print version record.
Keywords: Connectionism; PSYCHOLOGY -- Cognitive Psychology; SCIENCE -- Cognitive Science; Connectionism; Connectionisme; Cognitieve processen; Electronic books